A cohort study reporting clinical risk factors and individual risk perceptions of prostate cancer: implications for PSA testing. (21st June 2012) - Forbat, Liz; Place, Morag; Kelly, Daniel; Hubbard, Gill; Boyd, Kenny; Howie, Kate; Leung, Hing Y.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Prostate cancer has three known clinical risk factors: age, ethnicity and family history. Men's knowledge of prostate cancer is low. This study demonstrates that men rely on family and friends to learn about prostate cancer and help them interpret their risk. The findings suggest the need for tailored prostate cancer education, through social networks, to encourage risk‐stratified PSA testing, which will lead to earlier diagnosis for those most at risk. Objectives To determine men's perceptions of their risk of developing prostate cancer. To consider the implications for PSA testing based on individual risk perceptions. Patients and Methods The research adopted an embedded mixed‐method design, using clinical records and a retrospective postal survey. Patients (N = 474) diagnosed with prostate cancer in a two‐year period (2008–2009) in Greater Glasgow were identified from pathology records. In all, 458 men received a postal survey (16 deceased patients were excluded); 320 men responded (70%). Results Analysis indicates that there is no association between known clinical risk factors and men's perceptions of their own risk. Older men did not display increased perceived risk. Men with a family history of prostate cancer (11%) had no increase in their own perception of risk. PSA tests are not requested by those who are at greater risk. The subsample of patients who had requested a test were no more likely to have a family history of prostate cancer. They were more likely, however, to perceive themselves to be at high risk, to have friends with prostate cancer, to be affluent and to have a low grade tumour. Conclusions GPs need to balance men's risk perceptions in discussions about known clinical risk factors. Men's knowledge of prostate cancer stems largely from interpersonal sources (such as friends/family). Social networks may consequently offer an additional opportunity to increase awareness of risk‐stratified testing.